Probiotics in food safety and human health - Goktepe, Ipek (CRC Press/Taylor & Francis Group, 2006)
The discovery of new and previously unknown organisms that cause foodborne illness makes it essential for scientists, regulators, and those in the food industry to reconsider their traditional approaches to food preservation. A single source reference that can provide the latest practical information on how to deal with the range of probiotic health issues that have recently arisen would be invaluable to have.